Female senior secondary physics students’ engagement in science: a qualitative study of constructive influences - Oliver, Mary C.; Woods-McConney, Amanda; Maor, Dorit; McConney, Andrew (SpringerOpen, 2017)
Background: Prompted by fewer females compared to males enrolling in physics and advanced mathematics at both secondary and university levels, our research investigated the views and experiences of female students currently studying upper secondary school physics. We interviewed 18 female students about influences they considered important to their own science education, interest in science, and future science-related aspirations. Our purpose was to identify the experiences that these students most strongly associated with the generation and maintenance of their engagement in science, particularly represented in this research by their enrolment in upper secondary physics. Results: The research team used a systematic, iterative process to identify the main themes in the transcribed interview data. We identified the influence each girl reported as the strongest (ranked first). We also combined all influences that the participants had nominated, regardless of their ranking, to further examine all factors participants suggested as influential in their sustained engagement in school science (represented by their decision to study upper secondary physics). Systematic analysis of the interview data confirms that the influences on these females’ choices to study physics at upper secondary originate from a combination of their teachers, their school’s science culture, members of their family, the participants themselves and their peers. Conclusions: The interviews highlighted the idiographic complexities in understanding the wide range of important influences on these students studying physics at upper secondary school and their engagement in science. The unique contribution of this work is giving voice to the participants and reflecting on what these high achieving females have to say about the influential factors in their decisions to pursue science. Supportive teachers and the school science culture play essential roles, and other cultural and/or social factors such as family members and peers are identified as important. References to the culture and expectations of the school, family holidays, and conversations with siblings are support factors that seem to interact and overlap. At the same time, the importance of policy-amenable factors such as competent and caring science teachers, and science-supportive school cultures should be emphasised and encouraged.